2023
DOI: 10.1038/s41419-023-05735-x
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 deficiency in microglia accelerates photoreceptor cell death and immune cell infiltration following retinal detachment

Abstract: Retinal detachment (RD) occurs in several major retinal conditions and often causes irreversible vision loss due to photoreceptor cell death. Retinal residential microglial cells are activated following RD and participate in photoreceptor cell death via direct phagocytosis and the regulation of inflammatory responses. Triggering receptor expressed on myeloid cells 2 (TREM2) is an innate immune receptor exclusively expressed on microglial cells in the retina, and has been reported to affect microglial cell home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Evidence supporting the role of SAA in mitigating inflammatory responses also came from other studies. In fact, our previous studies showed that Saa3 was among the top upregulated genes in mouse model of retinal detachment and retinal degeneration 26 . It was shown that SAA regulates IL‐17 production 36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence supporting the role of SAA in mitigating inflammatory responses also came from other studies. In fact, our previous studies showed that Saa3 was among the top upregulated genes in mouse model of retinal detachment and retinal degeneration 26 . It was shown that SAA regulates IL‐17 production 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our previous studies showed that Saa3 was among the top upregulated genes in mouse model of retinal detachment and retinal degeneration. 26 It was shown that SAA regulates IL-17 production. 36,37 Further study demonstrated that SAA directly regulates Th17 cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation